Microprocessor Based Systems for the Higher Technician - Vears, R. E. (Newnes, 2016)
Microprocessor Based Systems for the Higher Technician provides coverage of the BTEC level 4 unit in Microprocessor Based Systems (syllabus U80/674). This book is composed of 10 chapters and concentrates on the development of 8-bit microcontrollers specifically constructed around the Z80 microprocessor. The design cycle for the development of such a microprocessor based system and the use of a disk-based development system (MDS) as an aid to design are both described in detail. The book deals with the Control Program Monitor (CP/M) operating system and gives background information on file handling. Programming is given attention through a thorough explanation of software development tools and the use of macros. Choosing devices from the Z80 family of processors, the author explains hardware development including topics on basic circuits for each stage of development in resonance with the applicable data sheets. When software and hardware are to be integrated and function efficiently, a technique called emulation may prove useful; hence it is also described. The book ends with troubleshooting or fault location, especially for computer systems that are still under development and riddled with bugs. Troubleshooting or fault location, which is considered an acquired skill, is improved with discussions on basic techniques, principles of operation, and the equipment needed for a successful diagnosis and solution of the problem. Software engineers, computer technicians, computer engineers, teachers, and instructors in the field of computing learning will find this book very instructive. The book can also be read by computer enthusiasts who desire to have an advanced technical know-how and understanding of computer hardware and systems.